Allochiria for spatial landmarks as the presenting feature of posterior cortical atrophy. (December 2022) - Luzzi, Simona; Fiori, Chiara; Ranaldi, Valentina; Baldinelli, Sara; Cherubini, Veronica; Morelli, Mauro; Silvestrini, Mauro; Snowden, Julie S.
Abstract: Allochiria refers to the mislocation of stimuli to the corresponding position on the opposite side of the body or hemispace. It is most often, although not exclusively, reported in the tactile modality and typically in association with unilateral neglect. We describe a patient presenting with a 2-year history of topographical disorientation without other cognitive complaints. We conducted a systematic exploration of his topographical problems to identify their cognitive substrate. Standard neuropsychological examination revealed no abnormalities. Notably, he performed well on perceptual, spatial, and constructional tasks. No signs of neglect were elicited. A tailored battery of tests was administered, involving road maps and landmarks, and designed to replicate the situations in which he experienced symptoms. The experimental tests showed no evidence of topographical agnosia or amnesia for landmarks and their spatial relationships and no hemispatial neglect. Nevertheless, the patient exhibited a systematic tendency to translocate topographical landmarks sited on the left to the right side. The phenomenon, consistent with representational allochiria, occurred exclusively for topographical landmarks, and was present along both personally familiar and new learned routes. Over the next two years more widespread visuoperceptual and spatial deficits emerged, with Balint and Gerstmann syndromes. Functional imaging revealed hypoperfusion of the occipito-parietal regions and amyloid PET the presence of amyloid plaques. A diagnosis was made of posterior cortical atrophy, the visual variant of Alzheimer's Disease. To our knowledge this is the first case of topographical disorientation presenting with selective representational allochiria and the first report of allochiria as an early sign of posterior cortical atrophy. The case sheds light on the cognitive basis of allochiria and on a puzzling clinical presentation of neurodegenerative brain disease.